ENROLLMENT EXTREMES IN HIGHER EDUCATION: OPERATIONAL CHALLENGES, MARKETING PARADOXES, AND STRATEGIC SOLUTIONS - Mirjalol Mirsobitov (Western European Studies, 2025)
This paper examines two increasingly prevalent yet contrasting enrollment dynamics in higher education: (1) over-enrollment leading to operational strain, and (2) under-enrollment despite substantial investment in student recruitment and marketing. Drawing on global trends and national case studies—including a fivefold increase in university enrollment in Uzbekistan between 2015 and 2025—the paper identifies how both scenarios expose structural weaknesses in academic planning, workforce capacity, and student services. Through a review of current literature and international practices, the analysis highlights the complexity of student decisionmaking and the limitations of transactional marketing approaches in education. The study calls for a shift toward integrated, evidence-based enrollment strategies that align institutional capacity with student engagement and emphasize long-term relationship-building over shortterm visibility
Keywords: engagement; emphasize; increasingly